2017
DOI: 10.18178/ijlll.2017.3.2.112
|View full text |Cite
|
Sign up to set email alerts
|

Impoliteness in Reader Comments on Japanese Online News Sites

Abstract: Abstract-Computer-Mediated Communication (CMC) has become an important part of human communication nowadays. When communicating using computers or digital media, people seem to behave differently when compared to face-to-face communication, especially in anonymous settings. When expressing their opinions in such an environment, people tend to write more directly and sometimes emotionally, without taking into consideration other people's face. Some may even be deliberately impolite or offensive on some occasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
1
0
1
Order By: Relevance
“…An earlier study conducted by the researchers revealed impolite strategies used by netizens in their discussions online [12], but these were not situated in a pandemic scenario. Impolite communication was also found in other studies and concurred by other scholars [13], [14]. At the school level, a preliminary study recently conducted of students' text messaging among themselves also revealed poor communication strategies, including rude expressions [15].…”
Section: 2supporting
confidence: 84%
See 1 more Smart Citation
“…An earlier study conducted by the researchers revealed impolite strategies used by netizens in their discussions online [12], but these were not situated in a pandemic scenario. Impolite communication was also found in other studies and concurred by other scholars [13], [14]. At the school level, a preliminary study recently conducted of students' text messaging among themselves also revealed poor communication strategies, including rude expressions [15].…”
Section: 2supporting
confidence: 84%
“…This needs to be highlighted, especially in the Malaysian context where English is the second language, as numerous research has pointed out that there is a tendency for non-native speakers to use fewer politeness strategies [20]. This scenario, coupled with the rising popularity of Computer-Mediated Communication (CMC), has brought about glaring impoliteness, especially in online communication [13], [14]. Maros and Liyana [21] explored politeness practice on Twitter based on [18] politeness strategies on their tweet updates and reported that the participants in their study employed all four strategies: bald-on record, positive politeness, negative politeness.…”
Section: Descriptions Of Politeness and Factors Influencing Politenessmentioning
confidence: 99%
“…Por un lado, en relación a la descortesía en Internet, se revisaron los trabajos de Wibowo & Kuntjara (2012), Dalton (2013) y Liu (2017); el primero correspondía a comentarios en línea en una página sobre fútbol (Okezone); el segundo, a comentarios en una página web de noticias (MSNBC.com), ya que se descartó el análisis realizado a unas transcripciones porque eran sobre conversaciones (HALO); y el tercero, a comentarios en una página de noticias japonesa (Ameba News). En este caso, las tres investigaciones (Wibowo & Kuntjara, 2012;Dalton, 2013;Liu, 2017) plantearon el estudio a partir del CMC que corresponde al Computer Mediated Communication. En la investigación de Wibowo & Kuntjara (2012), se analizaron 50 enunciados publicados en Okezone a partir de cinco estrategias de descortesía y se encontró que la única estrategia que no se utilizó en esta ocasión fue la de "retención de la cortesía" (p. 168).…”
Section: Estado De La Cuestiónunclassified